Effects of self-control training and brain endurance training on endurance performance and ratings of perceived exertion - Trafford, Daniel (My University, 2022)
Self-Control Training (SCT) and Brain Endurance Training (BET) are novel training modalities designed to enhance physical endurance by building fatigue resiliency. Despite their similarities, it has yet to be examined whether combining SCT and BET provides an additive or redundant/overlapping effect on endurance exercise performance. This study investigated the effects of SCT and combined SCT+BET on performance of a maximal exertion isometric resistance endurance task (high plank) and ratings of perceived exertion (RPE). Participants (N = 33) were randomized to engage in 4 weeks (18 training sessions) of SCT (isometric handgrip; n = 13), SCT+BET (10-minute cognitively demanding task, followed by SCT; n = 10), or no-training/control (n = 10). Isometric endurance performance trials were completed at pre-, mid-, and post-training. One-way analysis of covariance (ANCOVA) models were computed for each of the mid- and post-training trials (controlling for pre-training high-plank performance) to assess effects on performance. Results showed no significant effects of training on high plank performance between groups at mid-training; however, a large and significant effect for SCT compared to control was observed at post-training (p = .044, d = .961). No significant main effects or interaction effects were found for changes in RPE over time (p’s > .05). Findings support the use of SCT as an effective training method for physical endurance performance and suggest that BET may not offer additional performance benefit compared to SCT under the training and testing conditions used in this protocol. Future research should explore potential dose-response effects of SCT on performance and moderators such as trait self-control.
Keywords: Self-Control Training; Brain Endurance Training; Ego Depletion; Ratings of Perceived Exertion; Isometric Endurance Performance